Transformasi Budaya Organisasi dari Sistem Konvensional Menuju Sistem Berbasis Syariah - Fandi Ahmad Marlion; Himyar Pasrizal; Azifah Hidayati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The conventional organizational culture system that has developed so far tends to be solely oriented towards materialism, efficiency, and profit, often neglecting the dimensions of ethics, spirituality, and social justice. This study aims to analyze the process of organizational culture transformation from a conventional to a Sharia-based system, examining the supporting and inhibiting factors and the role of leadership in the transformation process. This study uses a qualitative-descriptive approach using the Systematic Literature Review (SLR) method. 19 pieces of literature were analyzed using thematic analysis, published between 2018-2026. The literature search was conducted systematically through several reputable scientific journal databases (Google Scholar, Sinta, Garuda, DOAJ, Scopus, and Springer). The results show that transforming organizational culture from a conventional system to a Sharia-based system is a complex process and requires a holistic approach. The transformation process must be carried out gradually and systematically, supported by strong internal factors, and led by visionary and values-based leadership. This research is limited to discussing organizational culture, change management, and sharia values ​​within organizations, and therefore does not specifically address positive law, state regulations, or fatwas in detail. It is recommended that future researchers explore state regulations in greater depth regarding the transformation of conventional organizational culture toward sharia.